AB1123 Bite Force Control in Subjects with Chronic Neck Pain. (10th June 2014) - Testa, M.; Geri, T.; Roatta, S.; Gizzi, L.; Petzke, F.; Falla, D.
Abstract : Background: Even if recent evidences suggest the absence of any relationship between body posture and dental occlusion in provoking spine or temporomandibular disorders, 1 electromyographic studies evidenciated a relationship between temporomandibular disorders and neck pain. Since pain disorders often affect the force production and control because of a feedback impairment, the neck pain might cause a deficit in bite force control. To date no studies were conducted to ascertain such a phenomenon. Objectives: To investigate the ability to control bite force in subjects with neck pain Methods: A sample of 13 subjects affected by chronic neck pain and 13 healthy subjects, age and gender matched, were recruited after informed consent. Two flexible force transducers housed in a soft envelope positioned between the first molars teeth constituted the force measuring device. The values of two Maximal Voluntary Contractions (MVCs) were used to generate 4 targets representing percentages (10, 30, 50 and 70%) of the right and left MVCs. The task required was to reach and hold for 5" the force targets randomly displayed on the monitor, by tuning the force exerted on both sides. The subject's force performance was measured using error indices from the reference target like the Mean Distance (MD) and Offset Error (OE). Between-group differences of the force errors (MD, OE) were analyzed using a wilcoxon rank sum test with alpha set at 0.05. Results: 13 subjects (10 females, 3 males) with neck pain and a matched control group participated in the study. There were no significant between-group differences in force production for both MD and OE. Conclusions: The neck pain subjects did not presented any significant difference in bite force control, compared with healty subjects. These results do not support an etiopathogenetic relationship between neck pain and temporomandibular disorders References: Rocha CP, Croci CS, Caria PH. Is there relationship between temporomandibular disorders and head and cervical posture? A systematic review. J Oral Rehabil. 2013 Nov;40(11):875-81. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.6029